2011
DOI: 10.1007/s13148-011-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Huntington’s disease through histone deacetylases

Abstract: Huntington’s disease (HD) is a debilitating neurodegenerative condition with significant burdens on both patient and healthcare costs. Despite extensive research, treatment options for patients with this condition remain limited. Aberrant post-translational modification (PTM) of proteins is emerging as an important element in the pathogenesis of HD. These PTMs include acetylation, phosphorylation, methylation, sumoylation and ubiquitination. Several families of proteins are involved with the regulation of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 276 publications
(317 reference statements)
0
16
0
Order By: Relevance
“…Many, though not all [55], studies have found that class I/IIa HDAC inhibitors have a beneficial impact on cellular, fly, and rodent models of Parkinson's disease [56][57][58][59][60][61][62][63]. HDAC inhibitors likewise have may have promise in Huntingon's disease, and other disorders caused by polyglutamine expansion in mutant neuronal proteins [64][65][66]. The mutant proteins which drive these disorder act within the nucleus to block histone acetyltransferase activities; hence, HDAC inhibitors can act in a compensatory fashion to restore a more appropriate level of histone acetylation [66][67][68].…”
Section: Ketones Modulate Protein Acetylationmentioning
confidence: 99%
“…Many, though not all [55], studies have found that class I/IIa HDAC inhibitors have a beneficial impact on cellular, fly, and rodent models of Parkinson's disease [56][57][58][59][60][61][62][63]. HDAC inhibitors likewise have may have promise in Huntingon's disease, and other disorders caused by polyglutamine expansion in mutant neuronal proteins [64][65][66]. The mutant proteins which drive these disorder act within the nucleus to block histone acetyltransferase activities; hence, HDAC inhibitors can act in a compensatory fashion to restore a more appropriate level of histone acetylation [66][67][68].…”
Section: Ketones Modulate Protein Acetylationmentioning
confidence: 99%
“…Although its precise mechanism of action remains unclear it is thought to involve an increase of the neurotransmitter gamma-aminobutyric acid (GABA) [101]. HDAC inhibitors are also being studied as possible treatments for polyglutamine diseases like Huntington's disease [102].…”
Section: Small Moleculesmentioning
confidence: 99%
“…Several reviews discussed the importance of various HDACs in specific NDs [17,18] and recently, HDAC6 was suggested to be a promising target for some of them [19]. In the present work, we aim at reviewing the published data regarding HDAC6.…”
Section: Introductionmentioning
confidence: 99%